2011
DOI: 10.3122/jabfm.2011.03.100171
|View full text |Cite
|
Sign up to set email alerts
|

The Colorado Asthma Toolkit Program: A Practice Coaching Intervention from the High Plains Research Network

Abstract: Introduction: Asthma is often under-diagnosed and under-treated in primary care. The Colorado Asthma Toolkit Program was initiated to establish a method for improving asthma care by providing to primary care practices coaching, training, and support for (1) evidence-based asthma diagnosis and treatment, and (2) education and activation of patients toward effective self-management of their illness.Methods: A collaborative program was initiated involving 2 academic medical institutions and the High Plains Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…75 The pre-post studies reported increases in the provision of action plans (27%-46%). [76][77][78]88 Both RCTs reported nonsignificant increases in patient education/asthma action plans (7% in 1 study; relative risk = 1.82 in the other study). 73,75 SOE: low.…”
Section: Multicomponentmentioning
confidence: 99%
See 3 more Smart Citations
“…75 The pre-post studies reported increases in the provision of action plans (27%-46%). [76][77][78]88 Both RCTs reported nonsignificant increases in patient education/asthma action plans (7% in 1 study; relative risk = 1.82 in the other study). 73,75 SOE: low.…”
Section: Multicomponentmentioning
confidence: 99%
“…Two of the 3 pre-post studies reported 25% to 49% increases in prescribing rates. 76,77 Three of the 4 RCTs reported no statistically significant effects.…”
Section: Multicomponentmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Practice coaches were used, a spirometer was given to the practices, and an interactive voice response program was created and provided. Through this ambitious program, these practices reported large increases in their appropriate diagnosis and management of asthma.…”
Section: Asthma Smoking and Steroid Dosingmentioning
confidence: 99%